2023
DOI: 10.3390/buildings13071595
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Phase Change Materials as a Heat Storage Medium for Cooling Applications in the Built Environment

Usman Masood,
Mahmoud Haggag,
Ahmed Hassan
et al.

Abstract: The air conditioning demand varies significantly in the hot and desert climates of the UAE due to diurnal temperature variation, seasonal shifts, and occupancy patterns. One of the challenges faced by the relatively higher energy-consuming UAE building stock is to optimize cooling capacity utilization and prevent excessive energy loss due to undesired cooling. A potential route to achieving such a goal involves cooling energy storage during low demand and releasing the stored cooling at peak demand times via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 202 publications
0
6
0
Order By: Relevance
“…The thermal energy storages that utilize the latent heat is called phase change materials (PCMs). 7) PCMs are considered attractive for solar applications, 8) space heating, cooling in buildings, 9) off peak energy storage, and heat exchanger improvements. 10) In this paper, we focus on nanometer-size PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal energy storages that utilize the latent heat is called phase change materials (PCMs). 7) PCMs are considered attractive for solar applications, 8) space heating, cooling in buildings, 9) off peak energy storage, and heat exchanger improvements. 10) In this paper, we focus on nanometer-size PCMs.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies as well as a literature review have shown that the incorporation of phase change materials (PCMs) at the envelope terminals (floors, walls, roofs, etc.) absorbs a large amount of thermal energy [16][17][18][19], which improves the thermal storage capacity [20][21][22] and improves air conditioning by absorbing and releasing heat through phase change [23,24]. Studies show that this approach is an effective scheme to reduce energy consumption and improve indoor air conditioning [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…For decades, PCMs, due to their useful properties, have been widely used as heat accumulators in installations using renewable energy sources (in particular solar radiation energy-photovoltaic modules) [4][5][6][7]; heat insulators in structural elements of buildings [8][9][10][11][12][13]; temperature stabilizers of food products or medicines (isothermal containers) [14][15][16]; temperature stabilizers of road surfaces [17][18][19]. The use of these materials in multilayer wall structures results in a reduction in daily temperature amplitudes inside the building and a delay in releasing the stored heat.…”
Section: Introductionmentioning
confidence: 99%